2010
DOI: 10.1136/jnis.2010.002246
|View full text |Cite
|
Sign up to set email alerts
|

Three dimensional CT angiography versus digital subtraction angiography in the detection of intracranial aneurysms in subarachnoid hemorrhage

Abstract: Sensitivity and specificity were higher than previously reported, suggesting that CTA may be used as an initial screening tool in lieu of DSA. Further studies are necessary to determine if CTA can supplant DSA in ruling out all forms of vascular disease in idiopathic SAH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 32 publications
1
23
0
2
Order By: Relevance
“…In the present work, women at their sixth decade of life consisted most of the patients as in some other studies [9,11,25,30]. The majority of studies have reported a female-to-male ratio of about 1.09-1.42 [23,31,32]. Some experts proposed the role of female hormones in female preference for non-traumatic intracranial hemorrhage but there is a controversy about this [33,34].…”
Section: Discussionmentioning
confidence: 48%
“…In the present work, women at their sixth decade of life consisted most of the patients as in some other studies [9,11,25,30]. The majority of studies have reported a female-to-male ratio of about 1.09-1.42 [23,31,32]. Some experts proposed the role of female hormones in female preference for non-traumatic intracranial hemorrhage but there is a controversy about this [33,34].…”
Section: Discussionmentioning
confidence: 48%
“…1b) [20]. Studies with recent technology have shown more promising results, with up to 99.6 % sensitivity on 16-slice CT scanners [21]. Xing et al [17] demonstrated an even higher sensitivity for small aneurysms on a 64-slice CT scanner than conventional nonrotational digital subtraction angiography; however, Wang et al [22] demonstrated an 81.8 % sensitivity for aneurysms smaller than 3 mm when performed on a 320-slice CT.…”
Section: Detection Of Cerebral Aneurysmmentioning
confidence: 99%
“…1), 8 of which met the inclusion criteria. 1,2,5,7,13,15,16,23 Results for these studies are summarized in Table 1. Three hundred sixty-eight patients, including those from the Groningen series, were eligible for the pooled analysis.…”
Section: Pooled Analysismentioning
confidence: 99%